Synergistic reinforcement of polyamide-based composites by combination of short and continuous carbon fibers via fused filament fabrication. (1st January 2019) - Peng, Yong; Wu, Yiyun; Wang, Kui; Gao, Guangjun; Ahzi, Said
Abstract: The aim of the present work was to study the synergistic reinforcement, by short and continuous carbon fibers, of polyamide-based composites. The three-phase composites were obtained by the fused filament fabrication process where short fiber reinforced polyamide was deposited/printed along with continuous carbon fibers in a layered structure. The properties of the continuous carbon fiber tows and short carbon fiber reinforced polyamide tows were first evaluated by means of morphological, thermal and mechanical tests. The effects of stacking sequence of laminates as well as the effects of both short and continuous fibers' contents, on the mechanical properties of laminated composites, were carefully analyzed by considering several layering configuration. The results showed that the synergistic reinforcement of laminates by both short and continuous carbon fibers was indeed superior to the individual carbon fiber reinforcement for the tensile strength but not for the elastic modulus. The tensile properties of the laminated composites were higher when the stacked continuous carbon fiber reinforced layers (CCFRLs) were separated. Laminated composites with more interfaces between short carbon fiber reinforced layers (SCFRLs) and SCFRL/CCFRL interfaces showed higher mechanical performance due to the stronger adhesion of these interfaces compared to the interfaces between CCFRLs. The mechanical properties of laminated composites tended to be higher with increasing continuous carbon fiber content. The rule of mixture was used to estimate the mechanical behaviors of short and continuous fiber reinforced composites. All the experimental data was comprised between the upper bound and the lower bound estimates. However, the experimental results were rather close to the upper bound due to the alignment of the continuous carbon fibers.